The use of digital hygiene in the professional activity of future mathematics and informatics teachers - Mark Koptyajev; Stoika Myroslav; Sztojka Miroszláv; Стойка Мирослав (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. In the modern era of digital interaction and constant use of information and communication technologies, digital hygiene emerges as a critically important component of the professional activity of future mathematics and informatics teachers. It involves the systematic observance of safe, ethical, and efficient practices for using digital resources to minimize risks associated with cyber threats, information overload, and breaches of privacy. One of the key aspects is digital literacy and safety-oriented behavior: knowledge about personal data protection, recognition of phishing and other forms of online fraud, use of strong passwords, and two-factor authentication. Studies show that among university students and staff, there is a significant proportion of individuals with insufficient knowledge and habits related to cyber hygiene, which highlights the need for specialized training [1]. A second important component is the regular updating of knowledge and skills, as technologies and threats are constantly evolving. Future teachers should incorporate self-education, participation in seminars, webinars, and cybersecurity courses into their professional practice. This will enable them not only to protect their own digital environments but also to serve as role models for their students. The third aspect is the integration of digital hygiene into the educational process and teaching methodology. This means that mathematics and informatics teachers should not only teach their subjects but also embed elements of digital hygiene into their lessons — for instance, explaining how to search for information safely online, how to verify sources, and how to respond to suspicious content. Educational tasks may also include practical exercises in evaluating the security of web resources or adjusting privacy settings on social media platforms. Research data obtained in different countries and contexts support the idea that the level of digital hygiene significantly correlates with age, educational background, and academic discipline. For example, a study conducted among students and staff of a Nigerian university found that while many respondents had broad access to the Internet, they lacked sufficient knowledge and behavioral skills in cyber hygiene [1]. Another study demonstrated how gender, employment status, and academic discipline influence awareness and practices of cyber hygiene among university communities [2]. In the context of professional training for future mathematics and informatics teachers, the implementation of digital hygiene should be systematic: introducing relevant modules or courses on cybersecurity and digital ethics into educational programs, organizing regular training sessions, practical workshops, and projects involving case studies of security or privacy violations. Collaboration with experts in information security and psychology is also essential for understanding risks and developing healthy digital habits.
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: digital hygiene; mathematics and informatics teachers; professional training